Eustachius’s Tabulae Anatomicae, in the 300dt anniversary of their publication by Lancisi in 1714 in Rome - Riva, A.; Conti, G.; Loy, F. (Italian Journal of Anatomy and Embryology, 2015)
Around 1550 Bartolomaeus Eustachius (1510?-1574), the great rival of Vesalius, joined the medical faculty of the University La Sapienza in Rome, and there are records that in the years 1555-1566 he held there the chair of Practical Medicine, where he had his pupil Pier Matteo Pini as first sector. During his lifetime Eustachius published only the Opuscola Anatomica (Venetiis 1563/64) containing six libelli (booklets) among which are of seminal importance those on kidney, teeth, auditory organ, and venous system. In 1552, under the direction of Eustachius and his assistant Pier Matteo Pini, 47 tables, then engraved in copper, were prepared by the Roman artist Giulio de’ Musi. Although they were treasured by Eustachius who bequeathed them to the family of Pini, they were unpublished and lost, though were searched repeatedly even by the great Marcello Malpighi. The plates were eventually found and acquired by Pope Clemente XI through the efforts of his physician Giovanni Maria Lancisi who published them in 1714 with new captions for the original had been lost. The title page also bears the beautiful engraving drawn by Pietro Leone Ghezzi from Ascoli, a painter of the papal court, and author of the official portrait of Pope Clement XI. Even though they became to be known more than one century and a half after their completion, the tables arouse such interest and praise among the most prominent scientists of the early XVIII century that, besides that by Lancisi, other editions, with new legends and comments, were printed from the original copper blocks or from re-engravings. Among the latter the best reproduced and commented are those by B.S Albinus, Leyden 1744, that became the anatomy reference book for the rest of the century. Through Albinus, a friend of Felice Fontana, Eustachius’s tables served, according to some critics, as models for the muscle figures in wax exhibited in the museums of La Specola in Florence and in the Iosephinum in Vienna.